Exposure to a 50-Hz magnetic field induced ceramide generation in cultured cells. (2nd April 2016) - Qiu, Liping; Feng, Baihuan; Ni, Zuowei; Wu, Xiaodan; Sun, Wenjun
Abstract: Purpose To investigate the effects of a 50-Hz magnetic field (MF) exposure on ceramide metabolism, as well as the cascade downstream signaling pathways in human amniotic (FL) cells. Materials and methods FL cells were exposed to MF at 0.4 mT for different durations (from 5–60 min). The ceramides levels were analyzed with high performance liquid chromatography tandem mass spectrometry (HPLC-MS/MS). The activity of cathepsin D was assayed using a fluorometric assay kit, and the activity of protein phosphatase 2A (PP2A) was examined by Western blotting. After exposing to MF at 0.4 mT for 60 min with sequential culture for different durations (0, 3, 6, 12 or 36 h), the rate of cell apoptosis was assessed by flow cytometry. Results Exposing cells to MF at 0.4 mT for different durations caused a significant increase in ceramide production via de novo synthesis and hydrolysis of sphingomyelin (SM), and the effect was different according to the exposure time. However, no significant change in cell apoptosis was detected after MF exposure for 60 min with sequentially culturing for up to 36 h. In addition, increase in ceramide did not activate its downstream signal molecules, cathepsin D and PP2A, which are usually closely related to apoptosis of cells. Conclusions Exposure to a 50-Hz MF could raise ceramide levels but had no significant effect on apoptosis in cultured cells.